Cliplets: Juxtaposing Still and Dynamic Imagery - Joshi, Neel; Metha, Sisil; Drucker, Steven; Stollnitz, Eric; Hoppe, Hugues; Uyttendaele, Matt; Cohen, Michael (Microsoft, 2012)
We explore creating “cliplets”, a form of visual media that juxtaposes still image and video segments, both spatially and temporally, to expressively abstract a moment. Much as in “cinemagraphs”, the tension between static and dynamic elements in a cliplet reinforces both aspects, strongly focusing the viewer’s attention. Creating this type of imagery is challenging without professional tools and training. We develop a set of idioms, essentially spatiotemporal mappings, that characterize cliplet elements, and use these idioms in an interactive system to quickly compose a cliplet from ordinary handheld video. One difficulty is to avoid artifacts in the cliplet composition without resorting to extensive manual input. We address this with automatic alignment, looping optimization and feathering, simultaneous matting and compositing, and Laplacian blending. A key user-interface challenge is to provide affordances to define the parameters of the mappings from input time to output time while maintaining a focus on the cliplet being created. We demonstrate the creation of a variety of cliplet types. We also report on informal feedback as well as a more structured survey of users.